Efecto de longitudes de estacas y niveles de área foliar en el enraizamiento de Sacha Inchi (Plukenetia Volubilis l.) en cámaras de Subirrigación - Vallejos Torres, Geomar (2008)
An alternative to meet the market demand with Sacha inchi is the establishment of plantations with selected productive features; however, there is the problem of lack seed of high genetic quality and enough quantity required for the oil industry, which makes that vegetative propagation acquires great importance. The objective of the present study was to evaluate the rooting ability of juvenile cuttings of sacha inchi (Plukenetia volubilis), using three length cuttings (4, 6 and 8cm) and four levels of leaf area (0, 25, 50 and 100 cm2), set to root in subirrigation propagators. The test was performed at the Peruvian Amazon Research Institute (IIAP) experimental nursery, San Martín, using a completely randomized block design with bifactorial comprised of 12 treatments, three replications and nine cuttings per experimental unit. At the end of the experiment (20 days from being established in the propagator), rooting percentages of 100% were obtained. The best rooting percentages were achieved with 8 cm long cuttings and leaf area of 50 to 100 cm2. In general, the species can be easily rooted in sand, using shade to allow 20% of light, which provides optimal average irradiation (74.46 lux), relative humidity (77.86%) and air and substrate temperatures (27.66 °C and 27.84 °C respectively) within the propagators.